Analysis of swimming teaching programs, aquatic competencies and specific skills in school settings from early childhood to secondary education: A systematic review - Alfonso Trinidad; Daniel Mendoza-Castejón; Laura Mercedes de la Calle; José Ángel del-Blanco-Muñiz (PLoS ONE, 2026)
The teaching of swimming in school contexts has become increasingly important due to the benefits in the integral development of students and the prevention of aquatic accidents.This study analyses, by means of a systematic review, the aquatic teaching programmes and Competencies implemented in school settings over the last 25 years, from infant to secondary education. The Methodological approach was based on the PRISMA guidelines, with searches in scientific databases (PubMed, Scopus, Sport Discus and Web of Science) and secondary sources. Sixteen studies were selected according to the PICOS model, assessed with the STROBE and TREND tools. The results show a predominance of technical-utilitarian approaches focused on specific swimming skills, with little curricular integration and limited involvement of PE teachers. Most of the studies focused on infant and primary school, being scarce in secondary school. A high variability in duration, frequency, Contents and Assessment instruments was evidenced. The studies highlight the need for greater inclusion of swimming in school curricula, with more comprehensive pedagogical approaches adapted to each stage. It is concluded that although progress has been made, systematic implementation is still limited, requiring greater institutional support, teacher training and methodological coherence.